La estimulación temprana en el desarrollo psicomotor de niños de Inicial 1 de la Unidad Educativa Vigotsky. - Parra Insuasti, Mishell Daniela (2024)
The present research aimed to propose an early stimulation guide for the psychomotor development of children of initial 1 of the Vygotsky Educational unit. In this endeavor, educators play a crucial role in implementing the guide and fostering the optimal development of their students. The methodological design used a qualitative approach, with correlational scope, a quasi- experimental and applied type design, of field and bibliographic. The population was made up of 51 students, with an initial of 2 and two teachers, who were in initial education. Participant observation was used as a data collection technique, as an instrument, and as an observation sheet with descriptors taken from the Portage Guide. The results show that children present a degree of maturity in terms of fine motor skills in the cut and coarse motor skills in the hand and eye coordination foot. This may have its explanation in the pandemic period that reduced social interaction with children of their age and, on the other hand, due to the genetic predisposition that we carry and that determines weaknesses in certain areas of development, in this case, psychomotor skills, however, it is the task of the educational field to carry out compensatory actions so that it does not negatively impact their general educational process. On the other hand, the scientific literature is abundant in evidence from previous studies that relate early stimulation in favor of psychomotor maturity.